NEED ANALYSIS: THE WRITING SKILL INSTRUCTIONAL MATERIAL CONTEXT FOR ACADEMIC PURPOSES - Audi Yundayani; Emzir Emzir; Zainal Rafli (English Review: Journal of English Education, 2017)
The required instructional material should be designed based on students needs. This study is intended toidentify 1) material design and organization, 2) language content, and 3) method and techniqueof the writing skill instructional material context for academic purposes which appropriate with studentscharacteristics and their situationrelated to the need of writing skills for academic purposes at non-English education study programs of STKIP Kusuma Negara Jakarta. The descriptive survey was used in identifying its material context through questionnaire, semi-structured interview and non-participant observation. The respondents were non-English education study programs students duringthe fifth semester in academicyear of 2016-2017.The result showed that 1) It is required to have clear and easily understandable writing instructional material for academic purposes; 2) The required language content is related to a)rhetorical-functional (descriptive, narrative, classifying and identifying); b) academic genres, in the forms of essay and report; c)writing process; d) summarizing; e) paraphrasing; 3) The method and techniques which are applied to instructional material must empower thestudents to practice a lot through communicative and applicative activities. Based on the findings, it can be concluded that need analysis should be the starting point in designing the instructional material, due to it is a process to determine students needs according to their wants, lacks, and necessities.Keywords: need analysis, writing for academic purposes, instructional material context